Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.talanta.2015.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of the Flavin group in choline oxidase. Insights and analytical applications for the determination of choline and betaine aldehyde

Abstract: Choline oxidase (ChOx) is a flavoenzyme catalysing the oxidation of choline (Ch) to betaine aldehyde (BA) and glycine betaine (GB). In this paper a fundamental study of the intrinsic fluorescence properties of ChOx due to Flavin Adenine Dinucleotide (FAD) is presented and some analytical applications are studied in detail. Firstly, an unusual alteration in the excitation spectra, in comparison with the absorption spectra, has been observed as a function of the pH. This is ascribed to a change of polarity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…As has been indicated above, we have use the FAD fluorescence of ChOx for the determination of Ch and BA, obtaining longer linear response range than for Glu [36]. In this case, the fluorescence of the FAD, as expected, decreased during the enzymatic reaction and the evolution of the fluorescence spectrum during the enzymatic reaction indicated that the reaction takes place in two consecutive, but partially overlapping, steps and each of them follows a different mechanism.…”
Section: Other Substratessupporting
confidence: 61%
See 1 more Smart Citation
“…As has been indicated above, we have use the FAD fluorescence of ChOx for the determination of Ch and BA, obtaining longer linear response range than for Glu [36]. In this case, the fluorescence of the FAD, as expected, decreased during the enzymatic reaction and the evolution of the fluorescence spectrum during the enzymatic reaction indicated that the reaction takes place in two consecutive, but partially overlapping, steps and each of them follows a different mechanism.…”
Section: Other Substratessupporting
confidence: 61%
“…We have also studied the spectroscopic properties of choline oxidase (ChOx, from both Alcaligenes sp and Arthrobacter globiformis) [36] during the enzymatic oxidation reaction of both, BA and Ch to GB, and also we find a remarkable behaviour of the ChOx fluorescence. Figure 13(A) shows the 3D spectra obtained with ChOx at pH = 6 before the reaction (FAD oxidized) and figure 13(B) shows the 3D spectra after the addition of a very high excess of BA (or Ch), when the enzyme is in the reduced form.…”
Section: The Concentrations Of the Intermediatesmentioning
confidence: 90%
“…The N-terminal 37 amino acids of FRDg that include the Dxx(s/t)(s/g)AS consensus motif [32] are sufficient as substrate for efficient flavinylation when fused to different proteins localised in the cytoplasm or in the glycosome. We also confirmed that Ser9 in this motif is essential for flavinylation [64], in agreement with Serebryakova et al [68,69], a broad functional pH range (4)(5)(6)(7)(8)(9)(10)(11) [70] and their small size -for iLOV approximately 10 kDa [71]. Other variants, such as miniSOG, can generate reactive singlet oxygen upon illumination, which is exploited for electron microscopy [72].…”
Section: Pyrrhocorissupporting
confidence: 90%
“…To trace a prominent endogenous auto-fluorescent band in T. brucei cell lines upon in-gel fluorescence analysis [49], we enriched the respective band by cell fractionation and identified it by mass spectrometry ( Figure S2) as the flavoprotein fumarate reductase (FRD). This explained the optical properties [8,9] and resistance of the fluorescence to denaturing conditions, as covalent flavin attachment to FRD had been reported in the closely related kinetoplastid L. pyrrhocoris [32]. The presence of an ApbE-like domain at the N-terminus of FRDg led to the hypothesis of covalent FMN attachment catalysed by a eukaryotic ApbE flavin transferase activity [32].…”
Section: Flavin Transferase Activity Of Trypanosome Frdgsupporting
confidence: 55%
See 1 more Smart Citation